Intense pulsed light, near infrared pulsed light, and fractional laser combination therapy for skin rejuvenation in Asian subjects: a prospective multi-center study in China - Tao, Li; Wu, Jiaqiang; Qian, Hui; Lu, Zhong; Li, Yuanhong; Wang, Weizhen; Zhao, Xiaozhong; Tu, Ping; Yin, Rui; Xiang, Leihong (Lasers in medical science, 2015)
Ablative skin rejuvenation therapies have limitations for Asian people, including post-inflammatory hyperpigmentation and long down time. Non-ablative lasers are safer but have limited efficacy. This study is to investigate the safety and efficacy of a combination therapy consisting of intense pulsed light (IPL), near infrared (NIR) light, and fractional erbium YAG (Er:YAG) laser for skin rejuvenation in Asian people. This study recruited 113 subjects from six sites in China. Subjects were randomly assigned to a full-face group, who received combination therapy, and split-face groups, in which one half of the face received combination therapy and the other half received IPL monotherapy. Each subject received five treatment sessions during a period of 90 days. Subjects were followed up at 1 and 3 months post last treatment. Three months after last treatment, the full-face group ( n = 57) had a global improvement rate of 29 % and 29 % for wrinkles, 32 % for skin texture, 33 % for pigment spots, 28 % for pore size, respectively. For patients in the split-face groups ( n = 54), monotherapy side had a global improvement rate of 23 % and 20 % for wrinkles, 27 % for skin texture, 25 % for pigment spots, 25 % for pore size, respectively. Both combination therapy and monotherapy resulted in significant improvements at the follow-up visits compared to baseline ( P < 0.001). Combination therapy showed significantly greater improvements compared to monotherapy at two follow-up visits ( P < 0.05). Combination therapy is a safe and more effective strategy than IPL monotherapy for skin rejuvenation in Asian people.